Raman instrument calibration for astromaterials and analysis of Mars return samples. (17th December 2022) - Jakubek, Ryan Scott; Fries, Marc D.
Abstract: The study of astromaterials generally involves the distribution of limited sample to many laboratories for analysis. Maximum scientific yield for a sample occurs when the data and results from different studies are examined as a collective. This collective examination of results will be particularly important for upcoming sample return missions including Mars sample return and OSIRIS‐REx. When comparing results across laboratories, instrument calibration is of key importance. For Raman data, this includes the calibration of all three Raman band parameters: peak wavenumber position, bandwidth, and intensity. Although wavenumber is routinely calibrated, bandwidth and intensity are not; though they are commonly compared across studies. In addition, Raman instrument calibration is time dependent. An understanding of the time dependence of instrument calibration is important for proper calibration. Here, we use a mixture of well‐established and recently developed calibration techniques to propose a standard method of calibrating Raman astromaterial data across laboratories to maximize the scientific value of the data.